Association of Group B Streptococcus (GBS) Serum Serotype-Specific Anticapsular Immunoglobulin G Concentration and Risk Reduction for Invasive GBS Disease in South African Infants: An Observational Birth-Cohort, Matched Case-Control Study. (20th December 2020) - Madhi, Shabir A; Izu, Alane; Kwatra, Gaurav; Jones, Stephanie; Dangor, Ziyaad; Wadula, Jeanette; Moultrie, Andrew; Adam, Yasmin; Pu, Wenji; Henry, Ouzama; Briner, Carmen; Cutland, Clare L
Abstract: Background: Licensure of a group B Streptococcus (GBS) polysaccharide-protein conjugate vaccine for protecting infants against invasive GBS disease (IGbsD) will likely need to be based on demonstrating vaccine safety in pregnant women, and benchmarking immunogenicity against a serological threshold associated with risk reduction of IGbsD. We investigated the association between naturally derived GBS serotype Ia and III IgG and risk reduction of IGbsD in infants ≤90 days of age. Methods: In a matched case-control study, IGbsD cases were identified from a cohort of 38 233 mother-newborn dyads. Mothers colonized vaginally with serotype Ia or III at birth and their healthy infants were eligible as matched controls. GBS serotype-specific anticapsular immunoglobulin G (IgG) was measured on maternal and cord blood/infant sera by multiplex Luminex assay, and the IgG threshold associated with 90% risk reduction of IGbsD was derived by estimating absolute disease risk. Results: In infants born at ≥34 weeks' gestational age, cord-blood IgG geometric mean concentrations (GMCs) were lower in cases than controls for serotypes Ia (0.05 vs 0.50 µg/mL; P  = .004) and III (0.20 vs 0.38 µg/mL; P  = .078). Cord-blood IgG concentrations ≥1.04 and ≥1.53 µg/mL were associated with 90% risk reduction of serotype Ia and III IGbsD, respectively. The maternal sera IgG threshold associated with 90% risk reduction was ≥2.31 µg/mL and ≥3.41 µg/mL for serotypes Ia and III, respectively. Conclusions: The threshold associated with a reduced risk for serotype Ia and III IGbsD identified on infant sera supports the case for licensure of a GBS polysaccharide-protein conjugate vaccine based on an immunogenicity evaluation benchmarked against the defined thresholds. Clinical Trials Registration: NCT02215226. Abstract : Infant serotype-specific anticapsular IgG concentrations ≥1.04 and ≥1.53 µg/mL were associated with 90% risk reduction of serotype Ia and III invasive group B Streptococcus (GBS) disease, respectively. These findings could assist in the licensure of a GBS polysaccharide-protein conjugate vaccine based on immunogenicity and safety.